2018
DOI: 10.1039/c8ce00754c
|View full text |Cite
|
Sign up to set email alerts
|

Simple design for metal-based halogen-bonded cocrystals utilizing the M–Cl⋯I motif

Abstract: The halogen bonding proclivity of the chlorine atom coordinated to the Co(ii) metal centre has been explored by synthesis and crystal structure analysis of a family of 12 novel metal-based halogen-bonded cocrystals with iodine-based donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…From the beginning of the intensive research into halogen bonding at the turn of the millennium [1][2][3][4][5], one of the main areas of interest (apart from the fundamental studies of the nature and properties of the halogen bond) has been to utilize the halogen bond as a reliable non-covalent molecular interaction in supramolecular chemistry in general [6][7][8][9], and particularly in crystal engineering [10][11][12][13][14], as a means of the deliberate design of multi-component organic [15,16] and metal-organic [17][18][19][20] materials, both comprising ionic species (salts) [21][22][23][24][25][26] and neutral molecules (cocrystals) [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…From the beginning of the intensive research into halogen bonding at the turn of the millennium [1][2][3][4][5], one of the main areas of interest (apart from the fundamental studies of the nature and properties of the halogen bond) has been to utilize the halogen bond as a reliable non-covalent molecular interaction in supramolecular chemistry in general [6][7][8][9], and particularly in crystal engineering [10][11][12][13][14], as a means of the deliberate design of multi-component organic [15,16] and metal-organic [17][18][19][20] materials, both comprising ionic species (salts) [21][22][23][24][25][26] and neutral molecules (cocrystals) [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In contrast, the use of halogen bonding in coordination complexes, which are among the most diverse structures found in chemistry, remains comparatively unexplored. 14 In the studies that have been reported, three general strategies have emerged: firstly the design of ligands with an acceptor and donor in the same ligand (type i), [15][16][17] secondly cocrystals with either a neutral or cationic complex and halogen bonding donors (type ii) [18][19][20][21][22][23][24] and lastly complexes with two different ligands with one acting as the acceptor and the other the donor (type iii). The latter class typically uses halopyridine ligands and chelates such as -diketonates to balance the charge of the metal and satisfy the need for octahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been substantial studies into halogen bonding in single component metal-organic solids [30][31][32][33][34][35][36][37][38][39][40][41], synthesis of multi-component materials based on halogen-bonded metal-organic components has been receiving much less attention. Particularly scarce are studies involving cocrystals of neutral metal-organic components acting as halogen bond acceptors [42][43][44][45][46][47]. The most promising building blocks to date have been metal coordination complexes comprised of pendant acceptor groups such as halogenide ligands [46,47], chelating ligands such as imines [43], β-dicarbonyl compounds [14] and ligands with additional (non-coordinating) electron rich atoms or groups such as morpholine or thiomorpholine [48,49], which can form cocrystals with halogen bond donors, such as perfluorinated iodobenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly scarce are studies involving cocrystals of neutral metal-organic components acting as halogen bond acceptors [42][43][44][45][46][47]. The most promising building blocks to date have been metal coordination complexes comprised of pendant acceptor groups such as halogenide ligands [46,47], chelating ligands such as imines [43], β-dicarbonyl compounds [14] and ligands with additional (non-coordinating) electron rich atoms or groups such as morpholine or thiomorpholine [48,49], which can form cocrystals with halogen bond donors, such as perfluorinated iodobenzenes.…”
Section: Introductionmentioning
confidence: 99%